2014
DOI: 10.1038/srep03779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antioxidants on the quality and genomic stability of induced pluripotent stem cells

Abstract: Effects of antioxidants on the quality and genomic stability of induced pluripotent stem (iPS) cells were investigated with two human iPS cell lines (201B7 and 253G1). Cells used in this study were expanded from a single colony of each cell line with the addition of proprietary antioxidant supplement or homemade antioxidant cocktail in medium, and maintained in parallel for 2 months. The cells grew well in all culture conditions and kept “stemness”. Although antioxidants modestly decreased the levels of intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…Recently, it has been found that high-dose antioxidants downregulates DNA repair-related kinases, which conversely results in genomic instability of iPSCs [21]. Therefore, adjusting the dose of supplementary antioxidants is critical.…”
Section: Induced Pluripotent Stem Cells (Ipscs)mentioning
confidence: 99%
“…Recently, it has been found that high-dose antioxidants downregulates DNA repair-related kinases, which conversely results in genomic instability of iPSCs [21]. Therefore, adjusting the dose of supplementary antioxidants is critical.…”
Section: Induced Pluripotent Stem Cells (Ipscs)mentioning
confidence: 99%
“…Some of the recent studies have sought to address nutritional requirements for pluripotency reprogramming and determined that some common dietary supplements have noteworthy potential for improving reprogramming efficiency and iPSC quality (Table , Fig. ).…”
Section: Nutritional Supplements For Pluripotency Reprogrammingmentioning
confidence: 99%
“…Relatively higher numbers of authentic-iPSCs following Vc treatment may in part be due to Vc-mediated transformation of partially reprogrammed pre-iPSCs into fully reprogrammed iPSCs (111). Furthermore, Stadtfeld et al 113,114 demonstrated that Vc treatment substantially improved the quality of iPSCs, reviving full developmental potential and unaltered genomic status (112). Generally, OSKM-transduced miPSCs bear altered epigenetic signatures at the imprinted Dlk1-Dio3 gene locus which modulates their ability to generate iPSC-derived adult mice through tetraploid complementation.…”
Section: Nutritional Supplements For Pluripotency Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, hiPSCs also seem to form teratomas faster and with higher aggressiveness than hESCs, irrespective of the site of administration or engraftment . Two new studies have observed that mitigation of oxidative stress during reprogramming and early passaging by using antioxidant supplements in the growth media was able to reduce genome instability in hiPSCs .…”
Section: Genetic Instability In Ipscsmentioning
confidence: 62%